Hambatan yang di Hadapi Guru SD dalam Merancang Modul Ajar di Kurikulum Merdeka - Aribah Capah; Khofifah Indah T; Fitri Mardayanti; Septi Qorima Sitorus; Tryona Loise Siahaan; Waliyul Maulana Siregar; Anggili Pratama (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Merdeka Curriculum was created as an effort to increase learning flexibility by tailoring learning materials to the unique needs and characters of each student. However, there are several obstacles that must be overcome before this curriculum can be implemented at the elementary school level, especially in terms of making learning modules. The purpose of this study is to find out the challenges that teachers face when creating lesson plans based on Merdeka Curriculum and the solutions that can be done. The research methodology used is a qualitative study by conducting a literature study. Based on the findings, the main challenges faced are the teachers' lack of understanding of project-based learning methods, differences in the structure of learning plans, lack of resources, and heavy administrative burdens. Merdeka Mengajar platform, continuous training, and reducing teachers' administrative burden are suggested solutions. This approach is expected to help teachers to create more creative and innovative teaching modules that are in line with Merdeka Curriculum principles.